Analisis Makna Jilbab: Sebuah Persepsi Mahasiswi IAIN Ponorogo (Pendekatan Analisis Semiotika Ferdinand De Saussure) - Zaimatul Millah (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2021)
The use of the hijab is a symbol in Islam that shows the piety of Muslim women. With the provisions of the syari'at which regulates that the veil is to cover the genitals. However, in the current era, the hijab is not only a covering of genitals, it is also a part of self-identity, life style and fashion in social interactions among society. That's why the hijab increases its function to beautify and value the beauty of its users. The development of the hijab in today's reality can change the way of thinking, the perception of the meaning of the hijab, especially among IAIN Ponorogo students. Saussure semiotic analysis is used to see the phenomenon of the meaning of the headscarf towards female students of IAIN Ponorogo. In this study, it was found that female students interpreted the hijab not only as an obligation to cover their genitals and self-identity for Muslim women, but also as a life style on the grounds that they looked fashionable and not too conservative.